Modeling Analysis of Economic Growth in Asia with a Dynamic Panel Approach Generalized Method of Moment (GMM) - Heppi Syofya (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: High growth is expected to overcome various economic problems. Therefore, various efforts have been made by the government in synergy with other related institutions as a form of optimization of economic growth. That is why economic growth is an important indicator for the development of a country. This study aims to analyze economic growth and the factors that influence economic growth in Asia during the 2000-2019 period using dynamic panels. Design/methodology/approach: The independent variables in this study are the human development index (HDI), changes in exports (PEXPORT) and government spending (EXPENGOV) using the GMM system method as a model for modeling economic growth. The GMM model system is the best model with Sargan testing. The data used in this study are in the scope of Asia with the number of observational studies that are 11 (eleven) with a total panel data turned on by the state observation system 209. Findings: The results show that the human development index (HDI) has a negative and significant effect on economic growth in Asia 2000-2019 period. Meanwhile, the export change variable (PEXPORT) and government expenditure (EXPENGOV) had a positive and significant effect on economic growth in Asia for the 2000-2019 period. Research limitations/implications: Furthermore, economic growth also strengthened the previous year's economic growth at a significance level of 1%. This shows that economic growth is economic growth, economy, economy, and state government spending. Originality/value: This paper is an original Paper type: Research paper